Variations in the sugar profiles of Brazilian stingless bee honeys as determined by ion chromatography: A preliminary study of the effect of bee species and botanical source - Zhang, Jiali; Yates, Hans S.A.; de Avelar Gomes, Cássia Regina; Nicodemo, Daniel; Fletcher, Mary T.; Marelli, Jean-Philippe; Hungerford, Natasha L. (Journal of food composition and analysis, 2025)
The honey of honeybees is the most used insect-produced food worldwide, and its physicochemical characteristics are well-known, facilitating quality control and commercialisation. However, stingless bee honey does not meet the established parameters for honeybee honey, and new research is needed to recognise the criteria for evaluation of these honeys. A distinguishing feature of stingless bee honey samples is the disaccharide trehalulose, a low glycemic index sugar that is becoming a biomarker for stingless bee honey authentication. This study assesses trehalulose levels and honey sugar content variation of fifteen different stingless bee species from Brazil, which has the greatest diversity of stingless bees in the world. The ion chromatography method achieved excellent separations of saccharides, including trehalulose, maltose and sucrose. Trehalulose was detected in honey samples from Melipona bees (below limit of quantitation to 2.79 %), Scaptotrigona bees (1.81 – 8.32 %), Tetragonisca bees (5.44 – 23.90 %), Plebeia bees (12.81 %), and Tetragona bees (24.68 – 39.03 %). Both bee species and local botanical sources potentially determine the trehalulose levels in stingless bee honey. In this sense, the definition of accepted limits for trehalulose in honey must be established per each species of stingless bee, based on a greater number of samples from different locations. [Display omitted] •Trehalulose compared in Brazilian stingless bee honey from 5 genera (15 species).•Quantitation of 10 sugars in these honeys by robust ion chromatography-based method.•Trehalulose is not a dominant sugar in the honey of every species of stingless bee.